Retrospective Clinical Evaluation of RMGIC/GIC Class V Restorations - Maria Jacinta M. C. Santos; Lucy Leon; Imad Siddique; Sheila Butler (MDPI AG, 2023)
The aim of this retrospective study was to evaluate the clinical performance of glass-ionomer cement (GIC) and resin-modified glass-ionomer cement (RMGIC) materials in Class V carious cervical lesions restored by dental students. Ninety-six (96) restorations performed with either GIC (Fuji IX) (n = 39) or RMGIC (Fuji II LC) (n = 57) were evaluated using the modified USPHS criteria by two independent investigators at two follow-up evaluations (two years apart). The Fisher statistical test was used to compare USPHS criteria and examine significant differences, with a significance level set at p < 0.05. The Kaplan-Meier algorithm was used to calculate the survival probability. The overall success rate of Class V restorations was 72.9% at the second follow-up evaluation, with restorations ranging in age from 2.5 to 3.5 years. The RMGIC (Fuji II LC) restorations exhibited a significantly higher overall success rate compared to the GIC (Fuji IX) restorations (p = 0.0104). Significant differences were observed in retention (p = 0.0034) and color match (p = 0.0023).